Cloning and nucleotide sequences of the homoserine dehydrogenase genes (hom) and the threonine synthase genes (thrC) of the gram-negative obligate methylotroph Methylobacillus glycogenes. - Motoyama, H (1994)
We have cloned the homoserine dehydrogenase genes (hom) from the gram-negative obligate methylotrophs Methylobacillus glycogenes ATCC 21276 and ATCC 21371 by complementation of an Escherichia coli homoserine dehydrogenase-deficient mutant. The 4.15-kb DNA fragment cloned from M. glycogenes ATCC 21371 also complemented an E. coli threonine synthase-deficient mutant, suggesting the DNA fragment contained the thrC gene in addition to the hom gene. The homoserine dehydrogenases expressed in the E. coli recombinants were hardly inhibited by L-threonine, L-phenylalanine, or L-methionine. However, they became sensitive to the amino acids after storage at 4 degrees C for 4 days as in M. glycogenes. The structures of the homoserine dehydrogenases overexpressed in E. coli were thought to be different from those in M. glycogenes, probably in subunit numbers of the enzyme, and were thought to have converted to the correct structures during the storage. The nucleotide sequences of the hom and thrC genes were determined. The hom genes of M. glycogenes ATCC 21276 and ATCC 21371 encode peptides with M(r)s of 48,225 and 44,815, respectively. The thrC genes were located 50 bp downstream of the hom genes. The thrC gene of ATCC 21371 encodes a peptide with an M(r) of 52,111, and the gene product of ATCC 21276 was truncated. Northern (RNA) blot analysis suggests that the hom and thrC genes are organized in an operon. Significant homology between the predicted amino acid sequences of the hom and thrC genes and those from other microorganisms was found.